Who Is Going for VCT? A Case Study in Urban Burkina Faso. (30th December 2012) - Kirakoya-Samadoulougou, Fati; Yaro, Seydou; Fao, Paulin; Defer, Marie-Christine; Ilboudo, François; Langani, Youssouf; Meda, Nicolas; Robert, Annie; Nagot, Nicolas
Abstract : Introduction . Voluntary HIV counselling and testing (VCT) is a key element of treatment and is essential for prevention of vertical HIV transmission. Little information is available on the uptake of VCT in Burkina Faso. This study aims to assess the prevalence of VCT in urban Burkina Faso, where the epidemic is still highly concentrated. Methods . We conducted a two-stage clustered population-based survey among 1, 694 subjects living in Ouagadougou, Burkina Faso. After informed consent was obtained, a behavioural questionnaire was administered to participants. Results . Overall, 10.2% of individuals had used VCT, while 9% were women. Among women who had a child after the launch of the programme to prevent mother-to-child transmission (PMTCT), only 10.4% have been tested for HIV. Almost all participants (99.3%) were aware of HIV/AIDS, and 65% knew the main methods of prevention. In multivariate analysis, older age and being married and better educated were independent factors associated with VCT. Conclusions . Despite high public knowledge and awareness about HIV, VCT uptake was still very low and PMTCT coverage was poor. New strategies are required to increase VCT uptake in urban areas, in particular among the youngest age.